TOTAL BAKTERI DAN KOLIFORM PADA MEDIA PERTUMBUHAN MAGGOT Black Soldier Fly KOMBINASI FESES SAPI PERAH, ENDAPAN SUSU DAN SAMPAH ORGANIK DAPUR - Fikri Alamsyah; Deden Zamzam Badruzzaman; Ellin Harlia (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2024)
Livestock industry waste and kitchen waste contain high levels of organic matter and are dangerous if not managed properly. To overcome this problem, bioconversion can be carried out using BSF maggot. This research aims to determine whether the growth media after being degraded by BSF maggots still contains bacteria and coliform that meet the requirements for solid organic fertilizer Kepmentan No. 261 Tahun 2019. The research was carried out experimentally with 4 treatments and 5 repetitions. Treatment consists of P0 = 100% organic kitchen waste, P1 = 50% dairy cow feces and 50% organic kitchen waste, P2 = 50% milk sludge and 50% organic kitchen waste, P3 = 33,33% dairy cow feces, milk sludge 33,33% and kitchen organic waste 33,33%. The data was analyzed using a paired t-test. The results for total bacteria and coliform before and after degradation of BSF maggot experienced a significant decrease (P<0,05) and fulfilled the requirements for Escherichia coli in the coliform group with a total of <102 MPN/g in the BSF maggot growth media.